The Compromised Mucosal Immune System of β7 Integrin-Deficient Mice Has Only Minor Effects on the Fecal Microbiota in Homeostasis - Babbar, Anshu; Hitch, Thomas C. A.; Pabst, Oliver; Clavel, Thomas; Hübel, Jessica; Eswaran, Sreepradha; Wagner, Norbert; Schippers, Angela (Frontiers in Microbiology, 2019)
The gastrointestinal tract is an ideal habitat for diverse bacterial species that reside in a homeostatic balance with local tissue and significantly contribute to host health. Negative shifts in gut microbiota profiles, also known as dysbiosis, may be implicated in the development of chronic disorders such as inflammatory bowel diseases (IBD). Adhesion molecule-dependent recruitment of immune cells to the gut is an important step in IBD pathogenesis. The adhesion molecule β7 integrin contributes to the development of the gut-associated lymphoid tissue (GALT), intestinal immune cell homing, and immune responses and is known to promote intestinal inflammation. Although many studies underlined the role of the gut microbiota in shaping the mucosal immune system, studies on the influence of the host immune system on the microbiota are rare, especially in homeostasis. We addressed this question via comparative 16S rRNA gene amplicon analysis of fecal microbial communities from wild-type and β7 integrin-deficient mice, the latter being characterized by a compromised GALT. Besides subtle increases in relative abundances of Muribaculaceae spp. and unknown members of the families Ruminococcaceae and Lachnospiraceae, there was altogether no major difference in microbiota profiles in β7 integrin-deficient mice vs. wild-type littermates. This indicates that, in conditions of homeostasis, there is only a minor influence of the host immune system on the fecal microbiota in our mouse model, stressing the potential importance of pathological factors for dysbiosis development.